Gypsum amendment as a means to reduce agricultural phosphorus loading: an economic appraisal - Iho, Antti; Laukkanen, Marita (MTT Agrifood Research Finland, 2012)
This study analyzes the economic feasibility of gypsum amendment as a means to reduce particulate and dissolved phosphorus loads from arable areas. To this end, an optimization model is developed that includes gypsum amendment as well as matching phosphorus fertilization to crop need and the level of soil phosphorus reserves as phosphorus load mitigation measures, with soil phosphorus reserves measured by soil test phosphorus (STP). The optimal extent of gypsum amendment is then determined simultaneously with optimal fertilization use as a function of field STP level. The results indicate that whether or not gypsum amendment is economically feasible depends on field erosion susceptibility and STP level. When accounting for the costs and benefits to the society on the whole, gypsum treatment suits best to mitigation of phosphorus losses from soils with excessively high phosphorus reserves; once a threshold STP level is reached, gypsum amendment is optimally given up. This threshold level depends on field slope and on society s willingness to pay for water quality.
Keywords: Ma; kipsi; maanparannusaineet; fosfori; ympäristövaikutukset; soil amendments; phosphorus; environmental impact; dynamic optimization; phosphorus fertilization; gypsum amendment; phosphorus loading; eutrophication